Bases para la construcción de un sistema de compra pública participativa (Tema Central) - Pérez Cárdenas, Marcela (2025)
Participatory Public Procurement is a State’s regulatory strategy for public procurement, which seeks to promote inclusion, equity and social dialogue by bringing certain communities or low-income people who were historically excluded from this market. Its purposes are to generate spaces for social participation, democratize income, highlight the role of certain subjects of special constitutional protection, break down inequalities, generate responsibility in the execution of public resources and contribute to the construction of the country. The purpose of this article is to study the CPP as a regulatory strategy for public procurement, which emerges as one of the various scenarios of participatory democracy, so it is not a recent policy but one that is under constant construction. In this sense, an analysis will be made of the PPP mechanisms with which participatory democracy has been reflected in Colombia in the state contracting scenario. It will also show the efforts of other countries in the region to promote inclusion in the public procurement market, to show that these are isolated and poorly systematized tools with tenuous effects. In any case, the recommendations of international organizations such as the OECD should be considered to achieve a better design and implementation of CPP instruments.